Lanthanum-modified iron tailing-based phosphate-removing adsorbing material and preparation method thereof

Through the preparation of lanthanum modified iron tailings-based phosphate removal adsorption materials, the problems of limited adsorption capacity and reduced efficiency in high-concentration phosphate-contaminated water bodies are solved, and efficient, stable and economical water body phosphate removal effect is achieved.

CN120132782AInactive Publication Date: 2025-06-13ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510274638.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2025-06-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When existing adsorption materials remove high concentrations of phosphate pollution in water, their adsorption capacity is limited and their adsorption efficiency decreases with the use time, which cannot meet the long-term use needs under complex water quality conditions.

Method used

By using iron tailings as the main raw material, combined with lanthanum chloride modification, walnut shell pore formation and other processes, a lanthanum modified iron tailings-based phosphate removal adsorption material with good pore structure was prepared. Lanthanum chloride modification improves the surface chemical properties and adsorption capacity of the material, and the walnut shell pore formation enhances the specific surface area and pore structure of the material.

Benefits of technology

This material significantly improves the adsorption capacity and stability of phosphate, can effectively remove high concentrations of phosphate in water, is suitable for long-term use under complex water quality conditions, and is low in cost, simple in process, environmentally friendly and efficient.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120132782A_ABST
    Figure CN120132782A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adsorption materials, and particularly discloses a lanthanum-modified iron tailing-based phosphate-removing adsorption material and a preparation method thereof. The lanthanum element is used for modifying the iron tailings, lanthanum chloride is adopted as a modifier, and the structure and surface performance of the material are optimized. After lanthanum modification, the specific surface area and the adsorption capacity of the iron tailings are remarkably improved, and phosphate in water can be effectively removed. Through reasonable design of a preparation process, the lanthanum modified iron tailing-based phosphate-removing adsorbing material prepared by the invention not only has relatively high adsorption performance, but also has relatively high stability, and is suitable for large-scale water body pollution treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of adsorption materials. More specifically, it relates to a lanthanum-modified iron tailings-based phosphate removal adsorption material and a preparation method thereof. Background Art

[0002] In the current field of environmental governance, water body phosphate pollution is a serious problem, especially the phenomenon of water body eutrophication is becoming more and more prominent. Phosphates mainly come from agricultural fertilization, domestic sewage and industrial wastewater discharges. Excessive phosphates can cause water body eutrophication, which in turn triggers a series of ecological problems such as algal blooms and fish deaths, seriously affecting water quality and destroying the ecological balance. Therefore, removing phosphates from water bodies has become a key technical problem in water pollution treatment. Current phosphate removal technologies mainly include chemical precipitation methods, biological treatment methods, and adsorption methods, etc. Among them, the adsorption method has been widely used because of its simple operation, low cost and environmental protection.

[0003] The adsorption method removes pollutants by adsorbing phosphates in water onto the surface of the adsorption material. However, existing adsorption materials such as activated carbon, industrial waste residues, natural minerals, etc., although they can remove phosphates at a certain concentration, they generally have problems such as unstable adsorption performance, low resource utilization rate, and high cost, and cannot meet the long-term use requirements under complex water quality conditions. Especially in waters polluted by high-concentration phosphates, the adsorption capacity of existing materials is limited, and the adsorption efficiency of many traditional materials decreases significantly with the increase of use time.

[0004] Iron tailings are solid wastes generated during the mining process, mainly composed of mineral components such as silicon, aluminum, and iron. Because iron tailings contain abundant iron oxides, they have certain adsorption properties, and are rich in resources and low in cost. Therefore, iron tailings, as a potential material, have been used to adsorb some pollutants in water bodies. However, unmodified iron tailings have poor effects in removing phosphates and cannot meet the high-efficiency removal requirements in water body treatment.

[0005] In view of the above related technologies, the inventor believes that although iron tailings have the potential to be used as adsorption materials, their own adsorption performance is still relatively limited, especially the effect of removing phosphates is poor, and they cannot replace the mainstream adsorption materials on the current market. Summary of the Invention

[0006] In the related technologies, the adsorption performance of iron tailings itself is still relatively limited, especially the effect of removing phosphates is poor, and it cannot replace the mainstream adsorption materials on the current market. To improve this defect, this application provides a lanthanum-modified iron tailings-based phosphate removal adsorption material and a preparation method thereof.

[0007] In a first aspect, the present application provides a lanthanum-modified iron tailings-based phosphate removal adsorbent material, adopting the following technical solution:

[0008] A lanthanum-modified iron tailings-based phosphate removal adsorbent material, wherein the adsorbent material is obtained by calcining green pellets at 600 - 800 °C for 40 - 80 min. The green pellets comprise the following components in parts by weight: 4.5 - 5.5 parts of powder base material, 1 - 2 parts of lanthanum chloride, 0.8 - 1.2 parts of pore-forming agent, and 1.5 - 2.5 parts of binder; the components of the powder base material include solid waste powder, and the solid waste powder includes iron tailings powder and iron tailings acid leaching residue. The pore-forming agent includes walnut shell powder, and the binder includes sodium silicate.

[0009] By adopting the above technical solution, the present application uses iron tailings as the main raw material, combines processes such as lanthanum chloride modification and walnut shell pore formation to prepare a ceramsite material with a good pore structure. As a modifier, lanthanum chloride can react with the mineral components in iron tailings to improve its surface chemical properties, thereby enhancing its adsorption capacity for phosphates. Lanthanum elements are evenly distributed in the porous structure of the ceramsite, enabling the material to have a high adsorption efficiency. In addition, the introduction of lanthanum chloride can also optimize the hydrophilicity and surface charge characteristics of the material, further enhancing the rate and capacity of the adsorption reaction, especially in the case of a high phosphate concentration in water, showing a significant removal effect. Walnut shell, as a pore-forming agent, plays an important role in the preparation of ceramsite. The organic components of walnut shell volatilize during the calcination process, leaving a large number of pores, forming a ceramsite with an excellent pore structure. By regulating the granulation and calcination processes, the specific surface area of the ceramsite is significantly increased, providing more effective sites for the adsorption of phosphates. Iron tailings acid leaching residue is the residue remaining after the acid leaching process of iron tailings, which has a higher porosity than iron tailings, facilitating the diffusion of phosphates in sewage into the interior of the adsorbent material. Through the synergistic effect of the above components, the lanthanum-modified iron tailings-based phosphate removal adsorbent material of the present application not only has obvious advantages in adsorption capacity compared with traditional adsorbent materials, but also has strong physical stability and chemical anti-interference ability. Moreover, by using waste resources, the adsorbent material of the present application has a low cost, a simple process, and is environmentally friendly and efficient. This material can be widely applied in the field of water pollution treatment, especially in waters with relatively serious phosphorus pollution, providing an economic and sustainable solution for water pollution treatment.

[0010] Preferably, the components of the powder base material further include palygorskite powder.

[0011] By adopting the above technical solution, the present application selects palygorskite powder as a component of the powder base material. After high-temperature calcination according to the technical solution of the present application, lanthanum chloride can modify palygorskite, realizing the loading of lanthanum on the surface of palygorskite powder particles. Moreover, the adsorption capacity of palygorskite powder itself can also be improved during the calcination process, which helps to enhance the effect of the adsorbent material in adsorbing phosphate.

[0012] Preferably, the weight ratio of the palygorskite powder to the iron tailings powder is (0.15 - 0.18):1.

[0013] By adopting the above technical solution, the present application optimizes the weight ratio of the palygorskite powder to the iron tailings powder, which helps to improve the effect of adsorbing phosphate.

[0014] Preferably, the components of the powder base material further include modified attapulgite clay, and the modified attapulgite clay contains magnesium chloride.

[0015] By adopting the above technical solution, the present application selects modified attapulgite clay containing magnesium chloride as a component of the powder base material. High-temperature calcination treatment can remove part of the crystal water in the modified attapulgite clay, increase the specific surface area of the attapulgite clay, and form active oxides such as magnesium oxide and calcium oxide. These active oxides can form precipitates with phosphate ions, thereby improving the adsorption effect of the adsorbent material on phosphate.

[0016] Preferably, the modified attapulgite clay is prepared according to the following method:

[0017] Mix attapulgite clay with magnesium chloride solution, wash with deionized water after oscillation treatment, then perform suction filtration, dry the filter cake in an oven, and then grind and screen the dried product to obtain modified attapulgite clay.

[0018] By adopting the above technical solution, the present application modifies attapulgite clay with magnesium chloride to obtain modified attapulgite clay containing magnesium chloride.

[0019] Preferably, the weight ratio of the modified attapulgite clay to the iron tailings powder is (0.06 - 0.08):1.

[0020] By adopting the above technical solution, the present application optimizes the proportion of the modified attapulgite clay to the iron tailings powder, which helps to improve the adsorption effect of the adsorbent material on phosphate.

[0021] Preferably, the average particle size of the powder base material is 50 - 85 μm.

[0022] By adopting the above technical solution, the present application optimizes the particle size range of the powder base material. Within the above particle size range, the ceramsite adsorbent material of the present application has good forming effect and adsorption performance.

[0023] Preferably, the powder base material further includes modified diatomite, and the modified diatomite is prepared according to the following method:

[0024] (1) Immerse iron tailings in nitric acid, then filter to separate the acid-leached residue of iron tailings and obtain an acid-leached solution. Add nitrate to the acid-leached solution and mix to obtain a modified acid-leached solution. In this step, the nitrate added to the acid-leached solution includes ferric nitrate;

[0025] (2) Add diatomite to the modified acid-leached solution, stir and heat, then let it stand for aging. After aging is completed, perform suction filtration on the obtained solid-liquid mixture, and dry and grind the separated solids to obtain modified diatomite.

[0026] By adopting the above technical solution, the present application uses nitric acid to leach iron tailings, obtaining an acid-leached solution and an acid-leached residue of iron tailings. The acid-leached residue of iron tailings can be used as a component of the solid waste powder, and the present application further modifies diatomite with the acid-leached solution. The metal ions leached in the acid-leached solution and the iron ions provided by ferric nitrate can change the surface electrical properties of diatomite, which is beneficial to the adsorption of phosphate ions by diatomite. In addition, the calcination treatment in the present application can also remove impurities in diatomite, making the pore structure of diatomite more suitable for adsorption. By preparing and adding modified diatomite according to the above method, the adsorption effect of the adsorption material of the present application on phosphate can be further improved.

[0027] Preferably, in the method for preparing the modified diatomite, the nitrate added to the acid-leached solution includes lanthanum nitrate.

[0028] By adopting the above technical solution, the lanthanum nitrate added to the acid-leached solution can be loaded onto the modified diatomite. The loading of lanthanum ions can increase the number of adsorption sites in the adsorption material, which helps to further improve the adsorption effect of the adsorption material on phosphate.

[0029] In the second aspect, the present application provides a method for preparing a lanthanum-modified iron tailings-based phosphate removal adsorption material, adopting the following technical solution.

[0030] A method for preparing a lanthanum-modified iron tailings-based phosphate removal adsorption material includes the following steps:

[0031] (1) Mix the powder base material, lanthanum chloride, pore-forming agent and binder, add deionized water and stir to obtain a raw material, and use a granulator to process the raw material. After natural air drying, obtain raw material balls;

[0032] (2) Preheat the raw material balls, and then calcine the raw material balls at 600 - 800 °C for 40 - 80 min to obtain a lanthanum-modified iron tailings-based phosphate removal adsorption material.

[0033] By adopting the above technical solution, the present application uses a simple and low-cost preparation process. By utilizing the mineral waste - iron tailings, it not only reduces the production cost but also reduces the environmental burden of the waste, meeting the requirements of resource reuse and environmental protection.

[0034] In summary, the present application has the following beneficial effects:

[0035] 1. The present application uses lanthanum element to modify iron tailings and adopts lanthanum chloride as the modifier to optimize the structure and surface properties of the material. After lanthanum modification, the specific surface area and adsorption capacity of iron tailings are significantly improved, and it can effectively remove phosphate in water. By reasonably designing the preparation process, the lanthanum-modified iron tailings-based phosphate adsorption material prepared in the present application not only has high adsorption performance but also has strong stability, and is suitable for large-scale water pollution treatment.

[0036] 2. The present application uses a simple and low-cost preparation process. By utilizing the mineral waste - iron tailings, it not only reduces the production cost but also reduces the environmental burden of the waste, meeting the requirements of resource reuse and environmental protection.

[0037] 3. Compared with traditional adsorption materials, the ceramsite adsorption material of the present application not only has low cost and simple process, but also can be mass-produced, and has high economic value. Generally speaking, the present application provides an efficient, environmentally friendly and sustainable large-scale water body phosphorus pollution treatment solution, providing strong support for water quality improvement and ecological protection. Description of the Drawings

[0038] Figure 1 It is the SEM image of the adsorption material in Example 1 of the present application.

[0039] Figure 2 It is the C1s peak (a), O 1s peak (b), Ca 2p peak (c), P 2p peak (d), La 3d peak (e) of the XPS image before adsorption of the adsorption material in Example 1 of the present application.

[0040] Figure 3 It is the C1s peak (a), O 1s peak (b), Ca 2p peak (c), P 2p peak (d), La 3d peak (e) of the XPS after adsorption of the adsorption material in Example 1 of the present application.

[0041] Figure 4 It is the N2 adsorption - desorption isotherm of Example 1 of the present application. Detailed Embodiments

[0042] The following further elaborates on the present application in conjunction with examples, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained through commercial channels.

[0043] Preparation Examples of Modified Attapulgite

[0044] The following takes Preparation Example 1 as an example for illustration.

[0045] Preparation Example 1

[0046] In this preparation example, the modified attapulgite is prepared according to the following method:

[0047] Mix attapulgite with 20wt% magnesium chloride solution at a weight ratio of 1:5, perform oscillation treatment at 25°C and 160 r / min for 24 h, then wash with deionized water, followed by suction filtration. After drying the filter cake, place it in an oven at 105°C for drying, and then grind and screen the dried product (using a 0.1 mm standard sieve) to obtain the modified attapulgite.

[0048] Preparation Examples of Modified Diatomite

[0049] The following takes Preparation Example 2 as an example for illustration.

[0050] Preparation Example 2

[0051] In this preparation example, the modified diatomite is prepared according to the following method:

[0052] (1) Add iron tailings to nitric acid with a pH of 3.2 at a solid-liquid ratio of 1:10, soak at 25°C for 24 h, then filter to separate the acid-leached residue of iron tailings to obtain the acid-leached solution. Add nitrate to the acid-leached solution and mix to obtain the modified acid-leached solution; in this step, the nitrate added to the acid-leached solution includes iron nitrate; in this step, the iron ion concentration in the modified acid-leached solution is 0.8 mol / L;

[0053] (2) Add diatomite to the modified acid-leached solution, stir and heat at 80°C for 48 h, then let it stand for aging for 12 h. After the aging is completed, perform suction filtration on the obtained solid-liquid mixture, and dry and grind the separated solid matter to obtain the modified diatomite.

[0054] Preparation Example 3

[0055] The difference between this preparation example and Preparation Example 2 is that in the method for preparing the modified diatomite, the nitrate added to the acid-leached solution further includes lanthanum nitrate, and the concentration of lanthanum nitrate in the modified acid-leached solution is 0.1 mol / L.

[0056] Examples

[0057] Examples 1 - 5

[0058] The following takes Example 1 as an example for illustration.

[0059] Example 1

[0060] In this embodiment, the average particle size of the powder base material is 100 μm. The components of the powder base material include solid waste powder, and the solid waste powder is composed of iron tailings powder and acid leaching residue of iron tailings mixed in a weight ratio of 5:1. The acid leaching residue of iron tailings is prepared according to the method of Preparation Example 2; the pore-forming agent includes walnut shell powder, and the binder includes sodium silicate.

[0061] This embodiment provides a lanthanum-modified iron tailings-based phosphate removal adsorbent material, which is obtained by calcining green balls at 600 °C for 80 min. The green balls include the following raw material components: 4.5 kg of powder base material, 1 kg of lanthanum chloride, 0.8 kg of pore-forming agent, and 1.5 kg of binder.

[0062] This embodiment provides a preparation method of a lanthanum-modified iron tailings-based phosphate removal adsorbent material, including the following steps:

[0063] (1) Mix the powder base material, lanthanum chloride, pore-forming agent and binder, add deionized water according to a water-to-material ratio of 1:4, stir to obtain raw material, and use a granulator to process the raw material. After natural air drying to constant weight, green balls with an average particle size of 2.5 mm are obtained;

[0064] (2) Heat the green balls to 300 °C at a rate of 5 °C / min, carry out preheating at 300 °C for 10 min, then heat to 600 °C at a rate of 5 °C / min, and calcine the green balls for 80 min to obtain the lanthanum-modified iron tailings-based phosphate removal adsorbent material.

[0065] As shown in Table 1, the differences between Examples 1-5 mainly lie in the raw material ratios and calcination conditions of the green balls.

[0066] Table 1 Raw material ratios and calcination conditions of green balls

[0067]

[0068] Example 6

[0069] The difference between this embodiment and Example 3 is that the components of the powder base material further include palygorskite powder, and the weight ratio of palygorskite powder to iron tailings powder is 0.1:1.

[0070] As shown in Table 2, the differences between Examples 6-9 lie in the weight ratios of palygorskite powder to iron tailings powder.

[0071] Table 2 Weight ratios of palygorskite powder to iron tailings powder

[0072]

[0073] Example 10

[0074] The difference between this example and Example 9 is that the components of the powder base material further include modified attapulgite, which is prepared according to the method of Preparation Example 1, and the weight ratio of the modified attapulgite to the iron tailings powder is 0.04:1.

[0075] As shown in Table 3, the difference between Examples 10 - 13 is that the weight ratio of the modified attapulgite to the iron tailings powder is different.

[0076] Table 3 Weight ratio of modified attapulgite to iron tailings powder

[0077]

[0078] As shown in Table 4, the difference between Examples 13 - 16 is that the average particle size of the powder base material is different.

[0079] Table 4 Average particle size of the powder base material

[0080] Sample Average particle size of powder base material / μm Example 13 100 Example 14 85 Example 15 70 Example 16 50

[0081] Example 17

[0082] The difference between this example and Example 16 is that the powder base material further includes modified diatomite, the weight ratio of the modified diatomite to the iron tailings powder is 1:10, and the modified diatomite is prepared according to the method of Preparation Example 2.

[0083] Example 18

[0084] The difference between this example and Example 17 is that the modified diatomite is prepared according to the method of Preparation Example 3.

[0085] Comparative example

[0086] Comparative Example 1

[0087] The difference between this comparative example and Example 1 is that the raw material balls do not include lanthanum chloride in their components.

[0088] Comparative Example 2

[0089] The difference between this comparative example and Example 1 is that the raw material balls do not include pore - forming agents in their components.

[0090] Comparative Example 3

[0091] The difference between this comparative example and Example 1 is that the raw material balls do not include acid - leached iron tailings residue in their components.

[0092] Performance detection test method

[0093] According to the requirements of "Molybdate Spectrophotometric Method for the Determination of Total Phosphorus in Water Quality" (GB 11893-89), potassium dihydrogen phosphate was used to prepare simulated phosphate wastewater with a total phosphorus content of 200 mg / L and an initial pH of 5.35. 10 g of adsorbent material was added to 1 L of simulated phosphate wastewater, and then it was placed in a rotary water bath thermostatic oscillator. The water environment temperature was set at 25 °C, the fixed oscillation time was 1200 min, and the oscillation rate was 150 r / min. After the oscillation ended, the supernatant was taken, and the absorbance was measured at 700 nm by the molybdate spectrophotometric method, and the phosphorus adsorption capacity was calculated. The results are shown in Table 5.

[0094] Table 5 Phosphorus adsorption capacity

[0095]

[0096] Combined with Examples 1-5 and Comparative Examples 1-3 and Table 5, it can be seen that the phosphorus adsorption capacities measured in Examples 1-5 are relatively high. This is because in this application, lanthanum element is used to modify iron tailings, lanthanum chloride is used as a modifier, and the structure and surface properties of the material are optimized. After lanthanum modification, the specific surface area and adsorption capacity of iron tailings have been significantly improved, and phosphate in water can be effectively removed. Through reasonable design of the preparation process, the lanthanum-modified iron tailings-based phosphate removal adsorbent prepared in this application not only has high adsorption performance but also strong stability, and is suitable for large-scale water pollution treatment. The iron tailings in Comparative Example 1 were not modified with lanthanum element, Comparative Example 2 was not modified by pore formation, and Comparative Example 3 lacked acid-leached slag of iron tailings rich in pores. Therefore, the phosphorus adsorption capacities of Comparative Examples 1-3 are relatively low.

[0097] Combined with Example 3 and Examples 6-9 and Table 5, it can be seen that the phosphorus adsorption capacities measured in Examples 6-9 are relatively high. This is because after high-temperature calcination according to the technical scheme of this application, lanthanum chloride can realize the modification of palygorskite, and lanthanum loading is achieved on the surface of palygorskite powder particles. Moreover, the adsorption capacity of palygorskite powder itself can also be improved during the calcination process, which helps to enhance the effect of the adsorbent on adsorbing phosphate.

[0098] Combined with Example 9, Examples 10-13 and Table 5, it can be seen that the phosphorus adsorption capacities measured in Examples 10-13 are relatively high. This is because high-temperature calcination treatment can remove part of the crystal water in the modified attapulgite, increase the specific surface area of attapulgite, and form active oxides such as magnesium oxide and calcium oxide. These active oxides can form precipitates with phosphate ions, thereby improving the adsorption effect of the adsorbent on phosphate.

[0099] Combined with Examples 13-16 and Table 5, it can be seen that when the average particle size of the powder base material is 50-85 μm, the ceramsite adsorption of this application can absorb phosphate more fully.

[0100] Combined with Example 16, Examples 17 - 18 and in combination with Table 5, it can be seen that the diatomite modified by adding the acid leaching solution of iron tailings can effectively improve the adsorption performance of the ceramsite adsorption material, and after adding lanthanum nitrate, the adsorption performance of the adsorption material can be further improved, which helps to fully remove phosphate pollutants in sewage.

[0101] Combined with Figure 1 -3, it can be seen that the lanthanum-modified iron tailings-based phosphate removal adsorption material (i.e., the ceramsite adsorption material) of the present application has a developed pore structure on its surface, and obvious phosphate spectral lines appear in the XPS diagram after the adsorption test, indicating that the adsorption of phosphate is fully realized during the test.

[0102] The above embodiments are only explanations of the present application, not limitations of the present application. Those skilled in the art can make modifications to the embodiments of the present application without creative contributions according to needs after reading this specification, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. A lanthanum modified iron tailings-based phosphate removal adsorption material, characterized in that: The adsorption material is formed by calcining raw balls at 600-800°C for 40-80 minutes, and the raw balls include the following components in parts by weight: 4.5-5.5 parts of powder base material, 1-2 parts of lanthanum chloride, 0.8-1.2 parts of pore formers, and 1.5-2.5 parts of adhesives; the components of the powder base material include solid waste powders, the solid waste powders include iron tailings powder and iron tailings acid leaching residues, the pore formers include walnut shell powder, and the adhesive includes sodium silicate.

2. The lanthanum modified iron tailings-based phosphate removal adsorption material according to claim 1, characterized in that: The powder base material also includes palygorskite powder.

3. The lanthanum-modified iron tailings-based phosphate removal adsorption material according to claim 2, characterized in that: The weight ratio of the palygorskite powder to the iron tailings powder is (0.15-0.18):

1.

4. The lanthanum modified iron tailings-based phosphate removal adsorption material according to claim 2, characterized in that: The powder base material also includes modified attapulgite, which contains magnesium chloride.

5. The lanthanum modified iron tailings-based phosphate removal adsorption material according to claim 4, characterized in that: The modified attapulgite is prepared according to the following method: The attapulgite is mixed with the magnesium chloride solution, washed with deionized water after oscillation, and then filtered. The filter cake is dried and placed in an oven for drying. The dried product is then ground and sieved to obtain modified attapulgite.

6. The lanthanum-modified iron tailings-based phosphate removal adsorption material according to claim 4, characterized in that: The weight ratio of the modified attapulgite to the iron tailings powder is (0.06-0.08):

1.

7. The lanthanum-modified iron tailings-based phosphate removal adsorption material according to claim 6, characterized in that: The average particle size of the powder base material is 50-85 μm.

8. The lanthanum modified iron tailings-based phosphate removal adsorption material according to claim 1, characterized in that: The powder base also includes modified diatomaceous earth, and the modified diatomaceous earth is prepared according to the following method: (1) adding iron tailings to nitric acid for soaking, then filtering, separating the iron tailings acid leaching residue to obtain an acid leaching solution, adding nitrate to the acid leaching solution and mixing to obtain a modified acid leaching solution; in this step, the nitrate added to the acid leaching solution includes ferric nitrate; (2) adding diatomaceous earth to the modified acid leaching solution, stirring and heating the solution, and then standing the solution for aging. After aging, the obtained solid-liquid mixture is filtered, and the separated solids are dried and ground to obtain modified diatomaceous earth.

9. The lanthanum-modified iron tailings-based phosphate removal adsorption material according to claim 8, characterized in that: In the method for preparing the modified diatomite, the nitrate added to the acid leaching solution includes lanthanum nitrate.

10. The method for preparing the lanthanum modified iron tailings-based phosphate removal adsorption material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) mixing a powder base material, lanthanum chloride, a pore-forming agent and a binder, adding deionized water and stirring to obtain a raw material, using a granulator to process the raw material, and obtaining a raw material ball after natural air drying; (2) preheating the raw material balls, and then calcining the raw material balls at 600-800° C. for 40-80 min to obtain a lanthanum-modified iron tailings-based phosphate removal adsorption material.